Prevention of Bullying on Children through the Integration of Character Education Values in Indonesian Folklores - Evi Chamalah,; Agus Nuryatin,; Suminto A,; Ida Zulaeha, (International Journal of Psychosocial Rehabilitation, 2020)
Bullying cases in Indonesia are still high, such as a case of children bullied for stealing a thing, bullied by their fellows, and mocked in cyberspace. In order to overcome this situation, the writers provided such ways for the prevention of bullying toward children through the integration of character education values in Indonesian folklores. This research used a qualitative-descriptive method with heuristic and hermeneutic reading on folklores from Semarang Regency, Indonesia. Based on the result of the research, it can be described that (1) forms of character education values on folklores in Semarang Regency, Indonesia, are (a) ‘religious’, (b) ‘honesty’, (c) ‘discipline’, (d) ‘hard work’, (e) ‘creative’, (f) ‘independent’, (g) democracy, (h) curiosity, (i) appreciation on achievement, (j) ‘communicative’, (k) social care, and (l) ‘responsible’ value; (2) ways to prevent bullying on children through integration of character education values in folklores from Semarang Regency, Indonesia, are as follows. These following ways could be done before the learning process. First, the teacher reads the folklores from Semarang Regency, Indonesia; secondly, the teacher reads the character education values contained in the folklores. What the teacher could do while teaching on a learning are, (1) the teacher reads the folklores for the students; (2) the teacher describes the character education values contained in the folklores to the students; and (3) the teacher invests or integrates values of character education in the folklores into the learning process.